Lysophospholipid Growth Factors and Their G Protein-Coupled Receptors in Immunity, Coronary Artery Disease, and Cancer. (2002) - Goetzl, Edward J.; Graeler, Markus; Huang, Mei-Chuan; Shankar, Geetha
Abstract : The physiological lysophospholipids (LPLs), exemplified by lysophosphatidic acid (LPA) and sphingosine 1-phosphate (S1P), are omnific mediators of normal cellular proliferation, survival, and functions. Although both LPA and S1P attain micromolar concentrations in many biological fluids, numerous aspects of their biosynthesis, transport, and metabolic degradation are unknown. Eight members of a new subfamily of G protein-coupled LPA/S1P receptors, originally termed Edg Rs, bind either LPA or S1P with high affinity and transduce a series of growth-related and/or cytoskeleton-based functional responses. The most critical areas of LPL biology and pathobiology are neural development and neurodegeneration, immunity, atherosclerosis and myocardial injury, and cancer. Data from analyses of T cells established two basic points: (1) the plasticity and adaptability of expression of LPA/S1P Rs by some cells as a function of activation, and (2) the role of opposing signals from two different receptors for the same ligand as a mechanism for fine control of effects of LPLs. In the heart, LPLs may promote coronary atherosclerosis, but are effectively cytoprotective for hypoxic cardiac myocytes and those exposed to oxygen free radicals. The findings of production of LPA by some types of tumor cells, overexpression of selected sets of LPA receptors by the same tumor cells, and augmentation of the effects of protein growth factors by LPA have suggested pathogenetic roles for the LPLs in cancer. The breadth of physiologic and pathologic activities of LPLs emphasizes the importance of developing bioavailable nonlipid agonists and antagonists of the LPA/S1P receptors for diverse therapeutic applications.